Experimental and Theoretical Investigation of Impinging Jet Ventilation at Different Cross Sectional Area of Supply Air Duct (Journal of University of Babylon for Engineering Sciences, 2018)
An experimental and computational analysis of temperature and velocity distribution in an office room have been studied. Office room of dimensions (3m x 1.75m x 3m) with two cross sectional types of supply air duct in the experimental part and three different cross sectional types of supply air duct in the theoretical part is usual as a tested model. The RNG k-  turbulence model was employed to solve the governing equations numerically and validated by comparing the numerical results with experimental data. The impinging jet concept has been proposed as a new ventilation strategy for use in office and industrial buildings. The present work focuses on evaluating the performance of a new impinging jet ventilation. In a theoretical study three types of supply air duct are adopted which are square supply air duct (Type-I), semi-elliptic supply air duct (Type-II) and rectangle supply air duct (Type-III) for two cases of air outlet terminal height from room foot level, 0.14h (case-I) & 0.1h (case-II). The third type (rectangle duct) gives lowest effective and discomfort conditions when compared with the other two types. This study investigated a number of factors influencing draught discomfort and temperature stratification in an office environment equipped with impinging jet ventilation IJV. The factors considered to be: shape of the air supply device, supply airflow rate and supply air temperature. Acceptable Air Distribution Performance Index (ADPI), effective temperature, and ventilation efficiency obtained that the square cross sectional area of supply air duct at 0.1h (case-II) height from foot level gives more acceptable indoor air quality and human thermal comfort when compared with the other types. Also, this type gives good air distribution system not only promotes a comfortable and healthy environment for occupants, but also contributes to energy conservation.